THE TROPHIC LINKS OF DRAGONFLIES (ODONATA) IN BIOCENOSES OF THE СENTRAL СAUCASUS - Kh. A. Ketenchiev; A. V. Tikhonova (Юг России: экология, развитие, 2014)
The trophic links of dragonflies in biocenoses of the Central Caucasus are examined in this article. The analysis of this phenomenon allowed to reveal the spectrum of the given connection of imago and larva’s members of the order Odonata in the communities of the study area. The structure of the trophic links is represented in the form of diagrams.